2D optical photon echo spectroscopy of a self‐assembled quantum dot. Issue 1 (28th December 2012) - Fingerhut, Benjamin P.; Richter, Marten; Luo, Jun‐Wei; Zunger, Alex; Mukamel, Shaul; Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> Simulations of two dimensional coherent photon echo (2D‐PE) spectra of self‐assembled InAs/GaAs quantum dots (QD) in different charged states are presented revealing the coupling between the individual mono‐exciton <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbs64v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Xq transitions and contributions of bi‐excitons <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbs639" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />XXq. The information about the <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbs60n" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />XXq states is crucial for various application scenarios of QDs, like e.g. highly efficient solar cells. The simulations rely on a microscopic description of the electronic structure by high‐level atomistic many‐body pseudopotential calculations. It is shown that asymmetric diagonal peak shapes and double cross‐peaks are the result of <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbs5zk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />XXq state contributions to the PE signal by analyzing the contributions of the individual pathways excited state emission, ground state bleach and excited state absorption. The results show that from the detuned <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbs5vx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Xq and <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbs5tc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />XXq contributions the bi‐exciton binding energies of the <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbs5st" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />XXq manifold are revealed in 2D‐PE signals.